MATERIALS USED IN THE ROAD BASES: METHOD OF THE RESIDUAL DEFORMATIONS’ CALCULATION - A. S. Aleksandrov; T. V. Semenova; N. P. Aleksandrova (Вестник СибАДИ, 2019)
Materials and methods. The authors performed the analysis of the models for calculating residual deformations accumulated by granular materials and under the influence of repeated loads. The research showed the hereditary nature of the strain granular materials’ accumulation. Therefore, the authors used integral calculus for analytical solution of the residual deformation’s dependence on the number of repeated loads and on the magnitude of the main stresses. Moreover, the authors obtained the solution in the form of logarithmic and power functions, which associated the accumulated deformation with the deformation arising from the first load application. In determining the deformation from the first load application, the authors took into account the model of the theory of plasticity, in which the elastoplastic deformation was determined by the sum of two components elastic and plastic, as well as rheological models considering the deformation as the sum of three or four components. Generalizing the model for various materials, the authors gave the preference to the model, in which the elastoplastic deformation was determined by four components: instantaneous elastic and residual deformations, elastic (elastic-viscous) deformation and a viscoplastic component. Therefore, the residual strain from the first load application was represented by the sum of the two components, instantaneous irreversible and viscoplastic. The viscoplastic component of the deformation was a result of stress relaxation in a relatively short period of time equal to the duration of the load impact. Such research allowed taking into account the effect of speed on the duration of the load and the magnitude of the viscoplastic component of the residual deformation. The authors emphasized that taking into account the viscous-plastic component of residual deformation was most appropriate when calculating residual deformations of soils and materials treated with an organic binder. Granular materials were less sensitive to viscoplastic deformation under a single load application, but, when the voltage exceeded the elastic limit, and the more plastic adaptability of crushed stone, gravel, etc. viscoplastic deformation made a significant contribution to the accumulated residual deformation.Results. As a result, the authors carried out the analysis of experimental data on the triaxial compression of various granular materials and determined the parameters obtained for the power and logarithmic functions. The authors studied such materials as granite, gneissic, granodiorite and diorite crushed stone, sand, gravel and crushed stone, gravel mixtures with a mineral part from various rocks and fortified sands.Discussion and conclusions. The paper demonstrates the possibility of using the solutions for calculation of the surface displacement of the pavement layers of granular materials. The authors formulate the tasks for further research.